Ecce homo : how one becomes what one is ; & the Antichrist : a curse on Christianity - Nietzsche, Friedrich Wilhelm, 1844-1900 (Classics series., 2004)
For some, the question remains: Why Nietzsche? Friedrich Nietzsche (1844-1900) was quite simply one of the most original and influential philosophers who ever lived; in addition, his writing style was brilliant, epigrammatic, idiosyncratic ["It is my ambition to say in ten sentences what everyone else says in a book - what everyone else does not say in a book."] The language dances, prances, whirls and twirls; it ranges from ghetto-verbalizations and vulgarizations to high art, from lyricism to sardonicism, from satyr-play to passion play. No one really writes like Nietzsche, though the number of his stylistic apes and imitators is legion (especially in the ranks of academe). Nietzsche, by the way, had nothing but contempt for academics; he considered them sterile mediocrities, puffed-up frogs in need of a pinpricking. This brings us to a second question: Why The Antichrist and Ecce Homo? Two of this great German's most germane offerings, they were among his last writings. Although he completed them both by the end of 1888, they were considered to be so inflammatory that they were published only years later, in 1895 and 1908, respectively. Both are products of Nietzsche's last creative year. Yet Ecce Homo is relatively calm and tranquil, while The Antichrist is a jeremiad full of venom and vitriol. The latter is in fact one of the most devastating condemnations of Christianity ever; Nietzsche calls it "the one immortal blemish on mankind," the greatest sin possible against reality, against the spirit of the earth. He goes on to say that "the first and last Christian died on the Cross." His analysis of Jesus and Paul as superlative Jewish types and his portrait of Pontius Pilate as a superior Roman type are thought-provoking, to say the least. This leads us to a third question: Why this translation? This version is more faithful than any other, thus, I think, better than any other. Every sentence has been weighed and sifted, sifted and weighed to reproduce Nietzsche's hybrid, high-bred style - that style which encompasses the shrill, strident, sarcastic and bombastic as well as the eloquent, impassioned, refined and resplendent. Nietzsche without tears, then, without scholarly excuses or pretentious "improvements"; Nietzsche without shortcuts; better yet, Nietzsche straight. Thomas Wayne is an English Professor at Edison College in Fort Myers, Florida. His translation of Nietzsche's Zarathustra was published in 2003 by Algora